Kesadaran Masyarakat Akan Kesehatan Anak Balita Melalui Posyandu Di Desa Mekarasih - Muhamad Rifqi Maulana; Rika Rahayu; Sendy Firdiasari; Siti Hartianti (Universitas Nusa Putra & Persatuan Insinyur Indonesia, 2024)
Community participation and public interest in utilizing Posyandu is still low, this is one of theproblems that hinders the implementation of health services through Posyandu. Community participation canaffect the sustainability of the Posyandu program to improve health services. The purpose of this study was todetermine community participation in this regard regarding the services of mothers who have toddlers in thePosyandu Mawar and Melati activities in Mekarasih, Simpenan District, Sukabumi Regency, West Java. Thisstudy uses a descriptive qualitative approach. The level of awareness of mothers who have toddlers is low due toinadequate facilities and poor schedule of posyandu so that people do not come to posyandu.